Odpowiedź :
a) 6*x-4+4*x=56
10x - 4 = 56
10x = 56 + 4
10x = 60 /:10
x=6
b) 2*x-3+x=9
2x - 3 + x = 9
3x - 3 = 9
3x = 9+3
3x = 12 /:3
x= 4
c) 3*x-5-x=12
3x - 5 - x = 12
2x - 5 = 12
2x = 12 + 5
2x = 17 /:2
x= 17/2
Odpowiedź:
A)
6x-4+4x=56
6x + 4x = 56 + 4
10x = 60
x = 60 : 10
x = 6
spr.
6x-4+4x=56
L = 6x - 4 + 4x = 6 * 6 - 4 + 4 *6 = 36 - 4 + 24 = 32 + 24 = 56
P = 56
56 = 56
L = P
B)
2x-3+x=9
2x + x = 9 + 3
3x = 12
x = 12 : 3
x = 4
spr.
2x-3+x=9
L = 2x - 3 + x = 2 *4 - 3 + 4 = 8 - 3 + 4 = 5 + 4 = 9
P = 9
9=9
L = P
C)
3x-5-x=12
3x - x = 12+ 5
2x = 17
x = 17 : 2
x = 8,5
spr.
3x-5-x=12
L = 3x - 5 - x = 3 * 8,5 - 5 - 8,5 = 25,5 - 5 - 8,5 = 20,5 - 8,5 = 12
P = 12
12 = 12
L = P
Szczegółowe wyjaśnienie: